Konsep Manajemen Mutu Internal sebagai Jaminan Peningkatan Mutu Sekolah di SMPN 13 Kota Jambi - Andini, Tyas Putri; Pratiwi, Dyah; Steffany, Becky Dwi; Saputri, Praditamega; Rahmawati, Amara Dwi (Universitas Batanghari Jambi, 2024)
The basic premise of this research is that standard management processes have not been implemented optimally, and standard management of teaching and learning collaboration has not been maximized, including many teachers who still have not mastered the use of information technology (IT) as a means of supporting learning. The aim of this research is to determine the planning, implementation and supervision of quality management in the provision of education at SMPN 13 Jambi City. This research uses a qualitative approach using the case study method, namely empirical research that examines a phenomenon in real life. The research results show that quality management in the provision of education at SMPN 13 Jambi City is carried out based on management functions. Quality management planning in the provision of education at SMPN 13 Jambi City refers to education management standards set by the National Education Standards Agency (BSNP) which reflect higher and competitive management standards. Implementation of a management program for the utilization of education and education personnel, namely the implementation of workshops, in-house training, coaching, a clear reward and punishment system for teachers, education personnel, students, and other financing that has not met the standards required to achieve educational quality.